DYSTOPIA AND ORWELL’S PITFALL IN GEORGE ORWELL’S 1984 (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2014)
George Orwell was ranked as one of the most influential English writers of the 20th century and as one of the most important chroniclers of English culture of his generation. George Orwell as a socialist criticized over a state or a government that claimed that, they are ideologically socialism. In this study, I discussed Dystopia and Orwell’s Pitfall in George Orwell’s 1984. Dystopia is an antithesis of utopia. If utopia is life of a society where a world in safe, happy, and others which are representing all of human dreams, it reflects the desire for seeking the age of the Queen of Justice, then dystopia is the world that became the symbol of human rights destruction of every man with their powerlessness and a hopeless life. This final project is aimed at how totalitarian dystopia reflected in 1984, what are the factors of George Orwell’s idea in 1984, and to identify how George Orwell’s adjusts himself due to his political position. I employ George Orwell’s 1984 as the object of this study. This study is a descriptive qualitative study with sociology in literature approaches. It is descriptive qualitative since the data of the study are in the form of phrases, sentences, narrations and dialogues and I do not employ computation. The data are gained by reading the novel thoroughly, identifying, and selecting. This investigation results in several findings. First, dystopia is really portrays in 1984 as the world deprivation. Second, Orwell wanted to show that basically people have a strong will to look for justice, love, truth, and solidarity. Third, Orwell wants socialism life is not a pure socialism, but socialism which represents the society that has freedom of speech. It can be concluded that Orwell is undogmatic socialist.